Leaching Efficiency of 238U and 232Th series from Granitic Soils - Ahmadi, Ahmad Zaher; Syazwan Mohd Sanusi, Mohamad; Afghan, Rahmatullah (Anuário do Instituto de Geociências, 2024)
Granitic soil, a uranium (U) and thorium (Th)-bearing soil body, can be sourced to extract fissionable nuclides through leaching using acidic solutions. Limited research indicates the feasibility of extracting U and Th from granitic sources, necessitating further studies to optimize leaching efficiency and its potential as a fissionable fuel. This study investigates the leaching efficiency of the uranium 238U and thorium 232Th series, as well as 40K, in granitic soil samples. The study utilized a high-purity germanium detector (HPGe) to quantify the activity levels of the 238U and 232Th series and 40K in the studied samples. The black sand deposit and tin-tailing samples were also utilized to benchmark the finding of the leaching efficiency of the uranium 238U and thorium 232Th in granitic samples. The study found that the leaching samples contained low radioactivity levels that were a few to tenth times lower compared to the original samples, with tin-tailing samples exhibiting the highest leaching activity for 238U (630.05 Bq l-1) and 232Th (512.17 Bq l-1) and comparable to granitic soil samples 238U (437.7 Bq l-1) and 232Th (23.9 Bq l-1). Sulfuric acid showed the most efficient leaching reagent ~ up to 23% and 32% for 232Th and 238U, respectively. In comparison, nitric and hydrochloric acids exhibited low leaching efficiencies, ~ 1 – 13%. Overall, granitic soil shows comparable leaching rates to conventional sources of natural uranium nuclear fuel, making it a potential secondary and alternative nuclear fuel source.